Rope of ash = Rentong - Shahnon Ahmad, 1933-2017 (Oxford in Asia modern authors, 1979)
Rope of Ash is set in the fictional village of Banggul Derdap, with its rice fields, wooden thatched houses and small mosque. It is a tale of bitter hatred, in which one family is pitted against the whole village in defence of what the family members believe to be traditional values relating to the soil.